A Multiposture Locomotor Training Device with Force-Field Control. (18th November 2014) - Sui, Jianfeng; Liu, Yali; Yang, Runze; Ji, Linhong
Abstract : This paper introduces a multiposture locomotor training device (MPLTD) with a closed-loop control scheme based on joint angle feedback, which is able to overcome various difficulties resulting from mechanical vibration and the weight of trainer to achieve higher accuracy trajectory. By introducing the force-field control scheme used in the closed-loop control, the device can obtain the active-constrained mode including the passive one. The MPLTD is mainly composed of three systems: posture adjusting and weight support system, lower limb exoskeleton system, and control system, of which the lower limb exoskeleton system mainly includes the indifferent equilibrium mechanism with two degrees of freedom (DOF) and the driving torque is calculated by the Lagrangian function. In addition, a series of experiments, the weight support and the trajectory accuracy experiment, demonstrate a good performance of mechanical structure and the closed-loop control.